Early Functional Recovery and Range of Motion After ACL Reconstruction: A Prospective Study Comparing Bone-Patellar Tendon-Bone vs. Hamstring Autografts - Saleh AbuMahara,; Hussein Rujbani,; Kefah Elmahdi,; Nusaiba Elhammal,; Mohamed Abdulwaret,; NasrEddine Shagloub, (AlQalam Journal of Medical and Applied Sciences, 2025)
Anterior Cruciate Ligament (ACL) reconstruction is commonly performed using either bone-patellar tendon-bone (BPTB) or hamstring autografts. Although long-term outcomes are often comparable, early postoperative recovery, including pain, range of motion, and functional recovery, may differ between graft types. This prospective cohort study compared early functional recovery, pain levels, ROM, and complications between BPTB and hamstring autografts in ACL reconstruction. Fifty patients were included: 30 received hamstring grafts and 20 received BPTB grafts. Early outcomes assessed included pain (visual analog scale, VAS), ability to walk without a limp, kneeling pain, time to return to sport/work, ROM, stiffness, and complication rates. Data were collected via structured questionnaires and clinical follow-up, with statistical analysis performed using independent t-tests and chi-square tests. Both groups exhibited minimal pain at rest (VAS = 0) and low pain during walking (VAS 0.3 vs. 0.5, p = 0.317). A high proportion achieved full extension (97% vs. 90%, p = 0.361) and full flexion (97% vs. 95%, p = 0.728), with no significant intergroup differences. Kneeling pain was slightly more frequent with hamstring grafts (33% vs. 30%, p = 0.815). Return to sport/work was significantly faster in the hamstring group (5.4 vs. 7.2 months, p = 0.048). Complication rates were low and comparable between groups (infection: 3.3% vs. 5%, p = 0.755; residual instability: 6.7% vs. 5%, p = 0.785). Early postoperative outcomes were similar between BPTB and hamstring autografts, with both providing excellent pain control, ROM recovery, and low complication rates. However, the hamstring group demonstrated a statistically faster return to sport/work. Graft selection should consider individual patient factors and surgeon preference.